Atypical Aortoesophageal Fistula with Atypical and Delayed Presentation and Negative Imaging Studies. (14th November 2016) - Hakim, Seifeldin; Gjeorgjievski, Mihajlo; Garg, Lohit; Orosey, Molly; Desai, Tusar
Abstract : A 59-year-old man with past medical history of thoracic aortic aneurysm treated with thoracic endovascular aortic repair presented with melena for 2 weeks. Initial EGD did not reveal the source of bleeding and showed normal esophagus; abdominal arteriogram did not reveal a fistulous communication and initial CTA showed normal position of the aortic graft stent without endoleak. The sixth EGD revealed a submucosal tumor-like projection in the upper esophagus and stigmata of recent bleeding. Another thoracic endovascular aortic repair with stent was placed over the old graft for presumed aortoesophageal fistula. Poststent upper gastrointestinal series with contrast showed extravasation of the contrast from the esophagus and CTA showed fistulous tract between aorta and esophagus. The patient refused definitive surgical repair despite having infected aortic graft; jejunostomy tube was placed and life-long suppressive antibiotic treatment was given and the patient is doing well at 2-year follow-up.